The first 20 hours of geopolymerization: An in situ WAXS study of flyash-based geopolymers - Williams, Ross; Van Riessen, Arie (mdpi, 2016)
This study followed the first 20 h of flyash geopolymerization at 70 °C using time resolved Wide Angle X-ray Scattering (WAXS). The extent of dissolution of the amorphous phase of the flyash was determined to range from 29% to 54% for the different formulations trialed. The dissolution rate of the flyash significantly reduced after the first 5 h for all samples. During the formation stage of the geopolymer there were significant temporal variations in the chemistry of the dissolved solution due to the rate of flyash dissolution, with a relative standard deviation of 20%, 57% and 24% for the Si/Al, Na/Al and H/Si ratios, respectively. Utilizing the Power Law, scattering in the low angle region of the WAXS pattern combined with the geopolymer peak area yielded a measure which correlated with the compressive strength-providing a new method to measure the flyash dissolution and geopolymer formation processes independently. The evolution of several zeolite-like phases was followed, noting there are different formation mechanisms involved even within the same sample. Four samples were examined with compressive strengths ranging from 14(2)-50(9) MPa, each was synthesized with flyash from Collie Power Station (Western Australia) activated with sodium silicate solution of varying concentrations.